2011
DOI: 10.1002/bsl.990
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acknowledging Mock Jurors' Feelings on Affective and Cognitive Biases: It Depends on the Sample

Abstract: An intervention designed to correct affective and cognitive biases was tested in the context of a civil commitment hearing of a sexually violent predator. Potential differences between a college student mock jury sample and a more representative, juror venire sample in reaction to these bias correction interventions were explored. In the first of two experiments, undergraduate mock jurors (n = 130) demonstrated a leniency effect when the sex offender's attorney acknowledged jurors' emotional reactions and moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…First, we sought to examine whether sample matters; that is, whether community jury panelists evaluated civil cases differently than undergraduate student panelists. Consistent with McCabe & Krauss (2011), we hypothesized that community members would provide larger punitive awards than students. We also expected that community members would show a greater lack of compartmentalization (i.e., more bleeding) between decisions on damages.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…First, we sought to examine whether sample matters; that is, whether community jury panelists evaluated civil cases differently than undergraduate student panelists. Consistent with McCabe & Krauss (2011), we hypothesized that community members would provide larger punitive awards than students. We also expected that community members would show a greater lack of compartmentalization (i.e., more bleeding) between decisions on damages.…”
Section: Introductionmentioning
confidence: 76%
“…Bornstein (1999) conducted a review of the research and found little evidence that studies with undergraduate mock jurors led to different results than studies with real jurors. However, in a recent study, McCabe & Krauss (2011) found important differences between the two samples. First, the authors gave a measure of rational processing to undergraduate students and community members and found that undergraduate students scored higher.…”
Section: Introductionmentioning
confidence: 90%
“…Other studies (e.g., McCabe & Krauss, 2011;McCabe et al, 2010) found that community samples are not affected by processing traits, but students are. Those studies were not death penalty studies, which might partially explain why the current study found no differences between students and community members but those studies did.…”
Section: Figure 3: Receiver Operating Characteristic Graph Area Undementioning
confidence: 95%
“…Specifically, undergraduates are generally younger, more educated, less punitive, have increased cognitive abilities, and are better at understanding the judge's instructions that might affect study outcomes (McCabe & Krauss, 2011;Wiener, Krauss, & Lieberman, 2011). Other researchers (Bornstein, 1999) have concluded that undergraduate students do not differ significantly from real jurors and can be used effectively for research.…”
Section: Limitations and Future Directionsmentioning
confidence: 98%